Redispersible spray-dried lipid-core nanocapsules intended for oral delivery: the influence of the particle number on redispersibility. (21st April 2018) - Andrade, Diego Fontana de; Vukosavljevic, Branko; Benvenutti, Edilson Valmir; Pohlmann, Adriana Raffin; Guterres, Sílvia Stanisçuaski; Windbergs, Maike; Beck, Ruy Carlos Ruver
Abstract: This study proposes a new approach to produce easily redispersible spray-dried lipid-core nanocapsules (LNC) intended for oral administration, evaluating the influence of the particle number density of the fed sample. The proposed approach to develop redispersible spray-dried LNC formulations intended for oral route is innovative, evidencing the needing of an optimization of the initial particle number density in the liquid suspension of nanocapsules. A mixture of maltodextrin and L-leucine (90:10 w/w) was used as drying adjuvant. Dynamic light scattering, turbidimetry, determination of surface area and pore size distribution, electron microscopy and confocal Raman microscopy (CRM) were used to characterize the proposed system and to better understand the differences in the redispersion behavior. An easily aqueous redispersion of the spray-dried powder composed of maltodextrin and L-leucine (90:10 w/w) was obtained, depending on the particle number density. Their surface area decreased in the presence of LNC. CRM enabled the visualization of the spatial distribution of the different compounds in the powders affording to better understand the influence of the particle number density of the fed sample on their redispersion behavior. This study shows the need for optimizing initial particle number density in the liquid formulation to develop redispersible spray-dried LNC powders.